TRANSFORMATION OF SHOROF LEARNING THROUGH INTEGRATION OF CLASSICAL AND INTERACTIVE DIGITAL MEDIA - Mahdi, Muhammad (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Learning Shorof for beginners often faces challenges, particularly in understanding word transformation patterns in Arabic. Traditional methods based on memorizing tashrif tables are often difficult to apply contextually. This study aims to analyze the integration of classical and interactive digital media in Shorof learning to enhance students' understanding. Using a qualitative literature study, this research examines the strengths and weaknesses of classical media, such as the Al-Amṡilatu Al-Taṣrīfiyyah book, and the potential of interactive digital media, such as educational videos and online quiz applications. The results show that integrating both media creates a more engaging, dynamic, and contextual learning experience. This approach not only preserves the depth of understanding from classical methods but also enhances student engagement through active interaction. This integration is expected to be an innovative solution for more effective and relevant Shorof learning in the digital era.